Anticancer Potency Studies of Coordination Driven Self‐Assembled Arene–Ru‐Based Metalla‐Bowls. Issue 5 (13th February 2014) - Mishra, Anurag; Jeong, Yong Joon; Jo, Jae‐Ho; Kang, Se Chan; Lah, Myoung Soo; Chi, Ki‐Whan
Abstract New tetranuclear cationic metalla‐bowls 5–7 with the general formula [Ru4(p‐cymene)4(N∩N)2(OO∩OO)2]4+ (N∩N=2, 6‐bis(N‐(4‐pyridyl carbamoyl)pyridine, OO∩OO=2, 5‐dihydroxy‐1, 4‐benzoquinonato (5), OO∩OO=5, 8‐dioxydo‐1, 4‐naphthaquinonato (6), OO∩OO=hoxonato (7)) were prepared by the reaction of the respective dinuclear ruthenium complexes 2–4 with a bispyridine amide donor ligand 1 in methanol in the presence of AgO3SCF3.These new molecular metalla‐bowls were fully characterized by analytical techniques including elemental analysis as well as 1H and 13C NMR and HR‐ESI‐MS spectroscopy. The structure of metalla‐bowl 6 was determined from X‐ray crystal diffraction data. A UV/visible study was also carried out for the entire suite of new complexes. As with recent studies of similar arene–Ru complexes, the inhibition of cell growth by metalla‐bowls was established against SK‐hep‐1 (liver cancer), AGS (gastric cancer), and HCT‐15 (colorectal cancer) human cancer cell lines. Inhibition of cell growth by 6 was found to be considerably stronger against all cancer cell lines than the anticancer drugs, doxorubicin and cisplatin. In particular, in colorectal cancer cells, expression of the cancer suppressor genes APC and p53 was increased following exposure to 6.